The Association of Physical Activity and Sleep Quality with Baroreceptor-Mediated Blood Pressure Regulation in Healthy Adult Women - Tatius, Bintang; Nabil Hajar; Herianto Sibuea (Sean Institute, 2025)
Baroreceptor-mediated blood pressure regulation is a vital autonomic mechanism influenced by various physiological factors, including physical activity and sleep quality. However, few studies have explored these relationships specifically in healthy adult women. This study aimed to examine the association between physical activity levels and sleep quality with baroreceptor function, measured through blood pressure changes from supine to standing positions. A cross-sectional analytical study was conducted involving 55 healthy adult women selected by purposive sampling from participants of community exercise programs at Klinik Pratama Unimus and Yayasan Al-Muqorrobin, Semarang. Participants completed the International Physical Activity Questionnaire (IPAQ) and Pittsburgh Sleep Quality Index (PSQI), followed by measurement of systolic, diastolic, and pulse pressure differences during the Schellong test. Baroreceptor response was operationalized as the difference in blood pressure and pulse rate from supine to erect positions. Data were analyzed using Spearman's rank correlation in SPSS version 25. A significant correlation was observed between physical activity levels and systolic blood pressure changes (r = 0.272, p = 0.045), as well as between sleep quality and diastolic blood pressure changes (r = -0.336, p = 0.012), indicating that higher physical activity and better sleep quality are associated with more stable baroreceptor responses. In conclusion, physical activity and sleep quality are significantly associated with baroreceptor-mediated blood pressure regulation in healthy adult women. Our findings suggest that lifestyle factors may play a role in maintaining autonomic cardiovascular function.